Not much helicity is needed to drive large-scale dynamos - Pietarila Graham, Jonathan (2012)
Understanding the in situ amplification of large-scale magnetic fields in turbulent astrophysical rotators has been a core subject of dynamo theory. When turbulent velocities are helical, large-scale dynamos that substantially amplify fields on scales that exceed the turbulent forcing scale arise, but the minimum sufficient fractional kinetic helicity f h,C has not been previously well quantified. Using direct numerical simulations for a simple helical dynamo, we show that f h,C decreases as the ratio of forcing to large-scale wave numbers k F/k min increases. From the condition that a large-scale helical dynamo must overcome the back reaction from any nonhelical field on the large scales, we develop a theory that can explain the simulations. For k F/k min≥8 we find f h,C3%, implying that very small helicity fractions strongly influence magnetic spectra for even moderate-scale separation. © 2012 American Physical Society.